Travel and tourism in the USA: industry development trends - Smal, Valentyna (Human Geography Journal, 2016)
The travel and tourism industry has evolved over the past six decades into one of the world’s most significant economic sectors. Travel and tourism are critical to the American economy. This growing industry offers significant potential for job creation across all regions of the country. A considerable competitive advantage of the USA as a tourism destination lies in the variety of experiences the country offers, ranging from large cities and small-town to the many unique historic places and ethnic heritage sites, national parks, camping, hiking, environmental or ecological sites, and well-known theme park.TheUnited Statesleads the world in revenues from international travel and tourism and ranks second in the number of international visitors. TheUnited Stateswelcomed nearly 75 million international visitors and received 177,2 billion dollars International Tourism Receipts in 2014.But the global travel market has become increasingly competitive. Other countries actively market themselves, and new destinations are aggressively competing for market share. According to World Bank data, the United States received 6,6% of global tourism arrivals in 2014 and accounted for nearly 14,2% of global spending on travel and tourism, down from 7,4% and 17%, respectively, in 2000. Because of that theU.S.market share of spending by international travelers has decreased and the government needs to work hard to support sectors of the economy such as the tourism industry. American experience is highly relevant for countries likeUkraine, which only seek their niche in the global tourism market.